The 100 most-cited articles on aortic dissection. Issue 1 (December 2017) - Lai, Ping; Liu, Yuan-hui; Xue, Jin-hua; He, Peng-cheng; Qiu, Yue-qun
Abstract Background To identify and characterize the most frequently cited articles that have been published on aortic dissection. Methods A list of the 100 most frequently cited publications (T100) about aortic dissection was generated by performing a searching of the Science Citation Index--Expanded using "aortic dissection" as the search term. Basic information about the articles was recorded, including number of citations, journal title, journal impact factor, time since publication, first author's country, topic/subspecialty of the research, and publication type. Results We finally included 180 articles on aortic dissection, from which we identified the 100 most frequently cited articles (T100). The most frequently cited article received 1079 citations, while the least frequently cited article received 68 (mean140.5 citations per article). The T100 originated from 19 countries, with more than half of them originating from the USA (n  = 97). The T100 articles were published from 1955 to 2013, with 79% published during the period 1990–2009. In addition, there were 40 different journals with Circulation having the most citations (n  = 38). Regarding the article type, there were 21 basic and 140 clinical research articles, one meta-analysis, and 18 review articles. Reviews had the highest mean number of citations (mean 235.5 citations per article). Conclusions Our study provides a historical perspective on the progress of dissection research, and helps to identify the quality of the work, the discoveries made, and the trends steering the studies.